Bone marrow‐derived mesenchymal stem cell‐loaded fibrin patches act as a reservoir of paracrine factors in chronic myocardial infarction. (3rd February 2017) - Blondiaux, Eléonore; Pidial, Laetitia; Autret, Gwennhael; Rahmi, Gabriel; Balvay, Daniel; Audureau, Etienne; Wilhelm, Claire; Guerin, Coralie L.; Bruneval, Patrick; Silvestre, Jean‐Sébastien; Menasché, Philippe; Clément, Olivier
Abstract: The combination of mesenchymal stem cells and tissue‐engineered fibrin patches improves the therapeutic efficacy of stem cells. In vivo cardiac magnetic resonance (4.7 Tesla) and ex vivo high‐spatial resolution CMR were used to track the fate of human bone marrow‐derived mesenchymal stem cell (BMSC) delivered on an epicardial scaffold and more specifically assess their potential intramyocardial migration. Fifty‐seven nude rats underwent permanent coronary artery ligation. Two months later, those with a left ventricular ejection fraction ≤55% were randomly allocated to receive a patch loaded with human BMSC (BMSC‐P, n = 10), a patch loaded with BMSCs labelled with iron oxide nanoparticles (BMSC*‐P, n = 12), an acellular patch (A‐P, n = 8) or to serve as sham‐operated animals (SHAM, n = 7). BMSC secretion of cytokines and growth factors was evaluated with flow‐cytometry. Cardiac functional parameters of cell‐treated groups (BMSC*‐P and BMSC‐P) yielded significantly better outcomes than the SHAM group ( p = 0.044 and p = 0.026, respectively, for ejection fraction). Angiogenesis was higher in the cell‐patch than in control groups (e.g. BMSC*P vs. SHAM: p = 0.007). No BMSCs were identified into the myocardium on cardiac magnetic resonance or histological sections, although persisting BMSCs were identified on the epicardial surface 21 days post‐transplantation in 10% of rats hearts (Lamin A/C and CD90 positive). Cytokine and growth factor profiling demonstrated an increase in their release by cells seeded in patches. The absence of stem cell migration into the myocardium and the persistence of stem cells on the epicardial surface suggest that fibrin patches are likely to act predominantly as reservoirs of paracrine factors. Copyright © 2017 John Wiley & Sons, Ltd.